A taste for corpora : in honour of Sylviane Granger - Meunier, Fanny; Granger, Sylviane, 1951- (Studies in corpus linguistics, 2011)
The eleven contributions to this volume, written by expert corpus linguists, tackle corpora from a wide range of perspectives and aim to shed light on the numerous linguistic and pedagogical uses to which corpora can be put. They present cutting-edge research in the authors' respective domain of expertise and suggest directions for future research. The main focus of the book is on learner corpora, but it also includes reflections on the role of other types of corpora, such as native corpora, expert users corpora, parallel corpora or corpora of New Englishes. For readers who are already familia.